Shrek the halls - Paramount Home Entertainment (Firm) ([United States] : Paramount Home Entertainment, 2008)
With no clue how to plan anything for the holidays, Shrek sets out to give Fiona and their children a perfect Christmas. With the help of a book and some party crashers, Shrek will learn what really matters.
Title from container.
Widescreen and fullscreen.
Special features: 12 days of Christmas sing-a-long ; Deck the halls sing-a-long ; Gingy's dunking game ; Shrek carnival craze video game demo & cheat code ; DreamWorks Animation video jukebox.
Rating: Not rated.
DVD.
English, French or Spanish dialogue; English, French or Spanish subtitles; closed-captioned.
Keywords: Monsters -- Juvenile drama; Ugliness -- Juvenile drama; Animated films; Children's films; Christmas films; Films for the hearing impaired